Kualitas permen jeli dengan pasta ekstrak bunga telang dan kulit buah kakao sebagai penstabil alami - Dian Ariani Saputra; Yuliana Reni Swasti; Franciscus Sinung Pranata (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Jelly candy is a popular treat for children, teenagers, and adults alike. The good qualities of jelly candy are its transparency, chewiness, and elasticity. Utilising Clitoria ternatea L. (butterfly pea) flower extract paste and cocoa pod extract paste (Theobroma cacao L.) to make jelly candy. This research aims to determine the quality of jelly candy with butterfly pea flower extract paste and Theobroma cacao pod extract paste in terms of its chemical, physical, microbiological, and panellist preference levels, and to determine the optimal concentration of butterfly pea flower extract paste and cocoa pod extract paste in making jelly candy. This study uses a completely randomized design with variations of butterfly pea flower extract paste and cocoa pod extract paste, 0:0 as control, 2:4, 4:6, and 6:8. Jelly candy in this research has a water content of 12.00-15.26%, a ash content of 0.12-0.35%, the antioxidant activity of 29.93-68.19%, hardness 44.20-66.05 N, springiness 0.96-0.97, and chewing power 34.54-58.32 N. The most preferred jelly candy was treatment A, which consisted of a 2% fruit peel extract paste and 1% butterfly pea flower. The total plate count and the number of yeast moulds met the quality requirements as specified in SNI 3547.2-2008. The optimal concentration of jelly candy paste is achieved using a combination of butterfly pea flower extract paste and cacao pod extract paste, with a ratio of 2:4.